From a National University to a National Higher Education System - Pavel Zgaga (Center for Educational Policy Studies Journal)
The article analyses the conceptualisations and gradual transformation of higher education in Slovenia from the 1980s to the early 1990s, i.e., during the period of profound social and political changes leading to the proclamation of the independent Republic of Slovenia in 1991. The broad public debate on the future of education in general was an important part of the awakening of civil society in the 1980s. In the specific field of higher education, intensive discussions led to the demand for a new and comprehensive development strategy. Given the profound transformation of higher education that took place during this period, this subject has been unjustifiably poorly researched. The article therefore tries to contribute to partially filling the gap, and at the same time to stimulating further research. Based on the study of archive material, the present analysis concludes that the most important innovation of this period can be defined as a gradual conceptual and then normative shift from a national university to a national higher education system.